Endocannabinoids Released in the Ventral Tegmental Area During Copulation to Satiety Modulate Changes in Glutamate Receptors Associated With Synaptic Plasticity Processes - Rodríguez-Manzo, Gabriela; González-Morales, Estefanía; Garduño-Gutiérrez, René (Frontiers in Synaptic Neuroscience, 2021)
EEndocannabinoids modulate mesolimbic dopamine neuron firing at the ventral tegmental area (VTA). These neurons are activated by copulation, increasing dopamine release in the nucleus accumbens (NAcc). Copulation to satiety in male rats implies repeated ejaculation within a short period (around 2.5 h), during which NAcc dopamine concentrations remain elevated, suggesting continuous neuronal activation. During the 72 h that follow copulation to satiety, males exhibit long-lasting changes suggestive of brain plasticity processes. Enhanced dopamine neuron activity triggers the synthesis and release of endocannabinoids in the VTA, which participate in several long-term synaptic plasticity processes. Blockade of CB1Rs during copulation to satiety interferes with the appearance of the plastic changes. Glutamatergic inputs to the VTA express CB1Rs and contribute to dopamine neuron burst firing and synaptic plasticity. We hypothesized that endocannabinoids, released during copulation to satiety, would activate VTA CB1Rs and modulate synaptic plasticity processes involving glutamatergic transmission. To test this hypothesis, we determined changes in VTA CB1R density, phosphorylation, and internalization in rats that copulated to satiety 24 h earlier as compared both, to animals that ejaculated only once and to sexually experienced unmated males. Changes in glutamate AMPAR and NMDAR densities and subunit composition and in ERK1/2 activation were determined in the VTA of males that copulated to satiety in the presence or absence of AM251, a CB1R antagonist. CB1R density decreased and the proportion of phosphorylated CB1Rs increased in the animals that copulated compared to control rats. CB1R internalization was detected only in sexually satiated males. A decrease in AMPAR density, blocked by AM251 pretreatment, and an increase in the proportion of GluA2-AMPARs occurred in sexually satiated rats. GluN2A-NMDAR expression decreased, and GluN2B-NMDARs increased in these animals, both of which were prevented by AM251 pre-treatment. An increase in phosphorylated ERK1/2 emerged in males copulating to satiety in the presence of AM251. Results demonstrate that during copulation to satiety eCBs activate CB1Rs in the VTA, producing changes in glutamate receptors compatible with a reduced neuronal activation. These changes could play a role in the induction of the long-lasting physiological changes that characterize sexually satiated rats.